An evaluation of energy balance parameters, and the relations between topographical and biophysical characteristics using the mountainous surface energy balance algorithm for land (SEBAL). Issue 13 (3rd July 2019) - Firozjaei, Mohammad Karimi; Kiavarz, Majid; Nematollahi, Omid; Karimpour Reihan, Majid; Alavipanah, Seyed Kazem
ABSTRACT: Energy balance parameters are very important in various applications such as energy global cycle, environment, climatic change monitoring, weather forecast, agriculture. The present study evaluates the influence of topographical conditions on the amount of downward shortwave radiation (SWD) of the surface, as well as the relation between surface Net radiation with biophysical characteristics and region's land use's. For this purpose, Landsat images, Digital Elevation Model (DEM), and a set of sample points have been used. To calculate the downward shortwave radiation and Net radiation fluxes, it has employed the mountainous SEBAL algorithm. Greenness, Brightness, Wetness, Normalization Difference Built-up Index (NDBI), Normalization Difference Vegetation Index (NDVI) and Albedo parameters considered as surface biophysical characteristics. Brightness, NDBI and Albedo information shows the percentage of impervious‏ surfaces while Greenness and NDVI information is related to vegetation percentage and Wetness information concerns water-related rates as well as the wetness of the soil, plant, and built-up lands. Statistical analysis has been used to study the relationship between different parameters. Results show that the slope is the most influential topographical parameters on the amount of SWD of the surface. There is a reverse relation between the variants of SWD of the surface, and the slope of the surface, in second-degree polynomial form with a Pearson's correlation coefficient ( r ) of 0.82. North aspect receive the minimum SWD average with a 681 W m –2 while flat lands receive the maximum SWD average with a 783 W m –2 . Areas with the highest elevation, lowest slope, and flatlands, receive the highest SWD. Built-up lands have the lowest Net radiation flux average with a 595 W m –2 while water has the highest Net radiation flux average with a 761 W m –2 . Net radiation flux is directly related with NDVI, Greenness and Wetness parameters, while it is reversely related to NDBI, Albebo and Brightness with a high r .